Penggunaan Filler Tanah (Silt) sebagai Perencanaan Campuran Aspal Beton AC-WC - Yando, Josua Robert; Panusunan, Panusunan; Fauzan, Fauzan (Jurnal Teknologi Riset Terapan, 2023)
Purpose: The rapid population growth in Batam City has increased traffic mobility, creating a demand for durable road pavement materials. Asphalt concrete, composed of bitumen and graded aggregates, depends on interlocking aggregate grains and filler as mortar for strength. This study evaluates the feasibility of using soil (silt) as a filler material, limited to 2%, in asphalt concrete mixtures. Methodology/approach: An asphalt concrete mixture was designed with soil filler and tested in the laboratory to determine optimal aggregate composition and specific gravity for each fraction. The mixture followed SNI, AASHTO, and ASTM standards, with analyses including aggregate gradation and density measurements for coarse, fine, and filler fractions. Results/findings: The optimal composition consisted of 31.55% coarse aggregate, 55.87% fine aggregate, and 6.88% filler. Specific gravity values were 2.632 g/cm³ for coarse aggregates, 2.615 g/cm³ for fine aggregates, 2.510 g/cm³ for rock ash aggregates, and 2.316 g/cm³ for soil fillers. All test results met standard specifications, indicating that soil filler can be effectively used in asphalt concrete mixtures. Conclutions: Asphalt concrete with 2% soil filler meets engineering standards and is suitable for road pavement construction in high-traffic areas. Limitations: This study only assessed soil filler up to 2% and focused on laboratory-scale tests. Field performance and long-term durability were not analyzed. Contribution: The findings provide an alternative, cost-effective filler material for asphalt mixtures, supporting sustainable road construction using locally available soil resources.